The future of European-Chinese raw material supply chains: Three scenarios for 2030 and their implications - Inga Carry; Nadine Godehardt; Melanie Müller (Stiftung Wissenschaft und Politik (SWP), 2023)
When it comes to being supplied with raw materials, Europe faces a number of challenges. These include the diversification of European supply chains, the implementation of effective sustainability standards, and the reduction of strategic dependencies on China. What will European-Chinese raw material supply chains look like in 2030? This paper outlines three possible scenarios, illustrating the combined effects of different political and socio-economic developments and the impact they could have on European-Chinese supply chains. It aims to help political actors gain a deeper understanding of possible future trajectories and map out appropriate policy strategies in response to different scenarios.
Keywords: 320; raw materials; diversification of European supply chains; effective sustainability standards; reduction of strategic dependencies on China; Sustainability Due Diligence Directive